2018
DOI: 10.1111/asj.13042
|View full text |Cite
|
Sign up to set email alerts
|

Conception rate of Holstein and Japanese Black cattle following embryo transfer in southwestern Japan

Abstract: This study aimed to quantify and compare conception rates to embryo transfer (ET) of Holstein and Japanese Black cattle in southwestern Japan. A 10-year retrospective epidemiological survey was conducted. The recipient numbers for Holstein and Japanese Black cattle was 621 and 527, respectively. Conception rates of Holstein and Japanese Black cattle during the study period were 45.4% and 42.3%, respectively. There was no significant difference between both breeds. However, a different trend of conception rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…CRs after embryo transfer in our study were 50.0% for fresh embryos and 47.5% for frozen–thawed embryos, very close to the corresponding values of 51.1% and 44.0% published for another herd of Japanese Black cattle [ 70 ]. CRs in the current study did not differ significantly across various breeds, including Simmental, Charolais, Brown Swiss, Holstein, or crossbreeds, which is consistent with a report of similar CRs between beef and dairy breeds [ 79 ]. The similarity in CR between fresh or frozen–thawed embryos in the Japanese Black cattle in the present study echoes previous results for Aberdeen Angus [ 80 ].…”
Section: Discussionsupporting
confidence: 92%
“…CRs after embryo transfer in our study were 50.0% for fresh embryos and 47.5% for frozen–thawed embryos, very close to the corresponding values of 51.1% and 44.0% published for another herd of Japanese Black cattle [ 70 ]. CRs in the current study did not differ significantly across various breeds, including Simmental, Charolais, Brown Swiss, Holstein, or crossbreeds, which is consistent with a report of similar CRs between beef and dairy breeds [ 79 ]. The similarity in CR between fresh or frozen–thawed embryos in the Japanese Black cattle in the present study echoes previous results for Aberdeen Angus [ 80 ].…”
Section: Discussionsupporting
confidence: 92%
“…The pregnancy rate after ET between June and September (the summer period) in the present study (40.3%) was similar to that in a previous study, which was performed during the same season in the same region (43.7%, n = 197) [71]. The pregnancy rate in the present study was within the range of previously reported pregnancy rates after ET during the hot season (14.3-55.4%) [20,21,[23][24][25][26][72][73][74][75], and higher than that of AI during the summer period in the commercial farms used in the present study (24.5%, n = 3863, data were obtained between 2016 and 2017) (unpublished data).…”
Section: Discussionsupporting
confidence: 90%
“…High temperature and humidity index (THI) (≥ 80) had a negative effect on the results of embryo transfer in the 8th, 7th and 6th day after heat [6]. Nabenishi et al [84] noted differences between CR in Japanese black and HF cattle in different seasons of the year. In Holstein-Friesian cattle the conception rates in August-October were lower than in other months.…”
Section: Environmental Factorsmentioning
confidence: 99%